2012
DOI: 10.1371/journal.pone.0046177
|View full text |Cite
|
Sign up to set email alerts
|

Promoted Neuronal Differentiation after Activation of Alpha4/Beta2 Nicotinic Acetylcholine Receptors in Undifferentiated Neural Progenitors

Abstract: BackgroundNeural progenitor is a generic term used for undifferentiated cell populations of neural stem, neuronal progenitor and glial progenitor cells with abilities for proliferation and differentiation. We have shown functional expression of ionotropic N-methyl-D-aspartate (NMDA) and gamma-aminobutyrate type-A receptors endowed to positively and negatively regulate subsequent neuronal differentiation in undifferentiated neural progenitors, respectively. In this study, we attempted to evaluate the possible f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 43 publications
(48 reference statements)
3
28
0
Order By: Relevance
“…Thus, it has been proposed that neurotransmitters may act directly as paracrine or autocrine factors to NPCs under physiological conditions. Indeed, systemic administration of NMDA decreases proliferation of NPCs in the adult murine hippocampal dentate gyrus [29], whereas administration of a dopamine D3 agonist increased proliferation of NPCs in the adult murine subventricular zone [28]. In the present study, we demonstrated the possibility that glycine enhances proliferation of NPCs.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Thus, it has been proposed that neurotransmitters may act directly as paracrine or autocrine factors to NPCs under physiological conditions. Indeed, systemic administration of NMDA decreases proliferation of NPCs in the adult murine hippocampal dentate gyrus [29], whereas administration of a dopamine D3 agonist increased proliferation of NPCs in the adult murine subventricular zone [28]. In the present study, we demonstrated the possibility that glycine enhances proliferation of NPCs.…”
Section: Discussionsupporting
confidence: 53%
“…extracellular glycine is effectively increased by blocking GLYT1 and that this mediates synaptic integration by dual activation of both the glycine receptor and the NMDA receptor [20,21]. Numerous previous studies have shown that proliferation of NPCs is regulated by activation of various receptors and these neurotransmitters; i.e., activation of the GABAA receptor, group I metabotropic glutamate (mGlu) receptor or dopamine D 3 receptor enhances proliferation of NPCs [22][23][24], whereas activation of the NMDA receptor, group III mGlu receptor, or α4β2 nicotinic acetylcholine receptor suppresses proliferative activity [25][26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…Abbreviations: CS, conditioned stimulus; No-Ext, Noextinction; NPE, non-pre-exposed; N.S., not significant; PE, pre-exposed; US, unconditioned stimulus. Takarada et al (2012) demonstrated that in undifferentiated neural progenitors, continuous exposure to nicotine led to a significant decrease in the capability to form neurospheres and subsequently accelerated neuronal differentiation. Another study showed that chronic administration of nicotine inhibited hippocampal neurogenesis in vivo, but had little effect on the differentiation of neuronal progenitors (Shingo and Kito, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the apoptotic effects of nicotine have been observed both in vivo and in vitro in the developing brain (Abreu-Villaca et al, 2004;Qiao et al, 2003). Continuous exposure to nicotine has been reported to have little effect on cell survival in neural progenitors in vitro (Takarada et al, 2012). Recent studies using DNA microarrays have shown that gestational nicotine exposure affects gene expression associated with cell adhesion and cell death/survival in the brains of adolescent rats (Cao et al, , 2013Wei et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation